Penggunaan Drone dalam Mengaplikasikan Pestisida di Daerah Sungai Besar, Malaysia - Hana Khoirunisa; Fitrianingrum Kurniawati (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Agriculture is an important thing that must be considered because all organisms including humans need food to live. In the industrial era 4.0 technology in the field of agriculture began to develop, starting from before planting to harvesting. In Sungai Besar, Selangor, Malaysia, almost all agricultural activities are already using machines and technology-based. One of them is the presence of drones owned by the Wawasan Tani Cooperative. Drones are used to apply pesticides or fertilizers to plants. Observation results show that spraying pesticides using drones is more effective and efficient because it can spray pesticides to plants is represent to the plant and the processing time can be two until twenty times faster. In addition, drones have also been developed to determine the state of plant health and identify pests and diseases in the field.